Recognising students who care for children while studying - Dent, Samuel (Emerald Publishing Limited, 2020)
Featuring a Prologue by Professor Penny Jane Burke, and Epilogue by Dr Ciaran Burke The often-changing definitions of widening participation groups in UK higher education has the potential to lead to inequitable experiences for students who do not fit into traditional typologies. This book considers the experiences of students who care for children while studying (CCS), a group often discussed only broadly in existing research, to shine a light on the unique barriers and experiences they face. Problematising 'who' is recognised in widening participation and equalities policy, Samuel Dent presents an Institutional Ethnographic study, involving 16 CCS students at a research-intensive UK University and collected over two academic years, to gain further insight into their institutional experiences. Unearthing the complex reality that CCS students' experiences vary in proportion to a diverse range of individual circumstances, Dent identifies a consistent theme in which these students experience a pattern of institutionally 'othering', 'individualisation', and 'passing' behaviours. Dent ultimately concludes by tackling the important question of how these patterns of experiential imbalance might be challenged.